If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t(t + -1) = 0 Reorder the terms: t(-1 + t) = 0 (-1 * t + t * t) = 0 (-1t + t2) = 0 Solving -1t + t2 = 0 Solving for variable 't'. Factor out the Greatest Common Factor (GCF), 't'. t(-1 + t) = 0Subproblem 1
Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing t to the left, all other terms to the right. Simplifying t = 0Subproblem 2
Set the factor '(-1 + t)' equal to zero and attempt to solve: Simplifying -1 + t = 0 Solving -1 + t = 0 Move all terms containing t to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + t = 0 + 1 Combine like terms: -1 + 1 = 0 0 + t = 0 + 1 t = 0 + 1 Combine like terms: 0 + 1 = 1 t = 1 Simplifying t = 1Solution
t = {0, 1}
| 0.5x+5=12.5 | | 4x(4+3y)-9(x+2xy)= | | 5(0.5x+2)=22.5 | | 22.5=10+2.5x | | 35.123/100 | | 5(e^2x)=7 | | 10x+23(x-5)=281 | | 6.5/39 | | (-6/-7)x(-5/3)x4 | | 3(x+7)-4x=12 | | -2(x+7)=6x-38 | | 6.2/0.05 | | (2/-5)(8)(-9/3) | | 5[1/2-x]=5/4 | | 9=0.2x*0.2x*0.6x | | 9=0.2x*0.2x*0.06x | | 8h-4h+2=78 | | 1-7x=7x-1 | | 7x+2=12.5 | | X^2+X-110+2(4)=8 | | 16/2=n | | 2(9x+5)=190 | | x^2-15x-44=7x+4 | | x^2+x-38=9x-5 | | 5x+2=x+3.6 | | x^2+11x+31=1 | | 5x=8y+1 | | -7x-1.6=-5-1.2 | | 8m-0=16 | | 4(6x-9)=180 | | -7.4-2.4=-6x-2.9 | | U=5(2W-4W^3+5W^2) |